Nilai-nilai Pendidikan dalam Novel Dhadhung Kepuntir karya Tulus S. (Pendekatan Sosiologi Sastra Swingewood) - Andriyanto, Octo Dendy; Supratno, Haris; Tjahjono, Tengsoe (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
The purpose of this research is to find social reflection on the novel Dhadhung Kepuntir by Tulus S., and the educational values ​​in the novel. This research is a qualitative descriptive study through the sociology approach of Swingewood literature. Content analysis and descriptive analysis were used as data analysis techniques. The data source used is the novel Dhadhung Kepuntir by Tulus S. The result of this research is that the novel Dhadhung Kepuntir reflects the social facts of Javanese society. This can be seen from the depiction; the languages, ethnic, the place, the socio-cultural background in the novel is like a description of finding a job. In addition, there are various educational values ​​that are reflected in the novel Dhadhung Kepuntir by Tulus S., including: persistence (patience, never giving up, working hard), caring values ​​(kinship, harmony, respect), religious values ​​(gratitude, noble, sincere). The depiction of the character Darmo who is always persistent in changing the fate to get the better life, can be inspiration for the younger generation to achieve their dreams. Keywords: education value; sociology of literature; reflection